Efektivitas Senam Otak (Brain Gym) terhadap Fungsi Kognitif pada Lansia - Nurli, Nurli; Ambo Hamzah, Idawati; Arfan, Farmin (Mando Care Jurnal, 2021)
Elderly (elderly) is someone who has reached the age of 60 years and over. The aging process in the elderly is marked by a biological setback that is seen as symptoms of physical, mental or psychological decline. Some actions that can be used to overcome memory decline include recognizing the abilities that are still possessed, individual therapy by doing cognitive therapy, group activity therapy and brain exercise. This research is a quantitative research method with a positive paradigm. The research design is pre-experimental with one group pretest posttest. The results of research that have been carried out show that brain exercise provides effective changes in cognitive function in the elderly. Before doing brain exercise, there was a 4.45% decline in cognitive function and then after doing research on brain exercise, cognitive function increased by 2.5%. One of the efforts to prevent decline in function in the elderly is to do brain exercise, there is an increase in cognitive function in the elderly after brain exercise is done.